2021
DOI: 10.7759/cureus.12786
|View full text |Cite
|
Sign up to set email alerts
|

Contact Lens Practices and Knowledge of Complications and its Association With Refractive Error in Saudi Arabia

Abstract: IntroductionFor optical, cosmetic, or therapeutic purposes, contact lenses (CLs) are temporary prostheses positioned on the eye. CLs do not only improve the quality of life by correcting, but also providing a better appearance and less activity restriction. Patients' failure to comply with the hygienic practices prescribed in using CLs is often considered an important risk factor for eye complications and it is not often clarified to CLs consumers at the time of dispensation. AimThe objective of this study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 14 publications
2
3
0
Order By: Relevance
“…Our results revealed that more than half of the participants were using contact lenses (56.2%). This finding is in agreement with many previous studies [8,11,[15][16][17], indicating that contact lenses are widely used taking into consideration the differences in the number of participants in each study. On the contrary, there was a lesser prevalence of contact lens use noted in other studies [17][18][19].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results revealed that more than half of the participants were using contact lenses (56.2%). This finding is in agreement with many previous studies [8,11,[15][16][17], indicating that contact lenses are widely used taking into consideration the differences in the number of participants in each study. On the contrary, there was a lesser prevalence of contact lens use noted in other studies [17][18][19].…”
Section: Discussionsupporting
confidence: 93%
“…Future research will require greater cross-sectional sampling and qualitative studies. The cross-sectional study is not an appropriate approach for establishing the causative associations among the study variables, which is consistent with what other authors found [8,11]. Also, non-response bias is a problem in such studies, consistent with other research [12].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Although we do not have a proper explanation for this correlation, except for the possible differences in demographics among these participants, previous studies have demonstrated the importance of education on obtaining better knowledge scores. [ 20 21 ] On the other hand, Alobaidan et al . [ 21 ] reported that neither gender nor the level of education significantly correlates with having high knowledge scores of CLs use in their Saudi general population, however, younger ages less than 25 years old did.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the usage of cosmetic eye lenses, we found that half of the sample indicated using lenses and 33% of the participants used them for cosmetic purposes. A study conducted in Saudi Arabia found the prevalence of contact lens usage among Saudi Arabians to be 15% [ 15 ]. Moreover, we found that 24.6% of participants rarely used eye cosmetic cleansers; 4.3% never used them at all and those showed statistically significant severity of DED.…”
Section: Discussionmentioning
confidence: 99%